Crisis Communication Management In Restructuring Programs - TOHA, Mohammad; RONDA, Mirza; WIDOWATI, Dewi (PT Keberlanjutan Strategis Indonesia, 2023)
One of the company's heavy burdens is being inefficient with an excessive number of employees, who ultimately become unproductive because they exceed the company's capabilities, namely both organic and non-organic employees/outsourcing. The research aims to analyze the role and efforts made by the PTKS Corporate Communication Division in the Restructuring program. The theories used are co-orientation theory and adaptive structural theory (AST). The method used is a case study, with data collection techniques through observation and interviews with several credible informants who know and are involved in this problem. The research results show that the role of PTKS Corporate Communication in managing crisis communications tends to be limited by the principal director of PT Krakatau Steel in terms of communication and publication to the public, especially to the media, to ensure that restructuring program information is released from one door. In this case, the leadership of the PTKS President Director was very dominant; at that time, only a few employees were allowed to speak to the public. It shows that in this restructuring program, the role of the Corporate Communication Division is different from the task description set by the company.